2018
DOI: 10.1177/0885066618788019
|View full text |Cite
|
Sign up to set email alerts
|

Hospital-Acquired Infections in Critically Ill Patients With Cancer

Abstract: Hospital-acquired infections are a common and costly problem facing critically ill patients in the intensive care unit (ICU). Critically ill patients with cancer are a particularly vulnerable subpopulation who possesses additional, nonmodifiable risk factors for developing these infections and, in many cases, are at increased risk of death as a result. This review will describe the most common nosocomial infections patients with cancer acquire while in the ICU: ventilator-associated events, central line-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
0
19
0
1
Order By: Relevance
“…Pseudo-outbreaks (or pseudo-epidemics) are real clusters of false infections or artifactual clusters of real infections. 2 The pseudo-outbreak described here was caused by false-positive urinary-antigen test results. Community pseudooutbreaks of this kind have been reported previously.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Pseudo-outbreaks (or pseudo-epidemics) are real clusters of false infections or artifactual clusters of real infections. 2 The pseudo-outbreak described here was caused by false-positive urinary-antigen test results. Community pseudooutbreaks of this kind have been reported previously.…”
mentioning
confidence: 85%
“…To the Editor-Central venous catheter (CVC)-related bloodstream infections (CRBSIs) are clinically important healthcareassociated infections. 1,2 To reduce the burden of CRBSIs, many countries have implemented national surveillance programs. 3,4 Reliable epidemiological data are provided not only by cohort studies but also by randomized controlled trials (RCTs), [5][6][7] which are considered the gold standard for assessment of clinically relevant questions.…”
mentioning
confidence: 99%
“…Expectedly, cancer patients have improved outcome due to better-quality and value-added available therapies; however, as these patients are critically ill, exposed to multiple treatments, and longer hospital days, consequently escalating number of patients are exposed to the HAI [26]. The HAI are paramount concern among cancer patients as they are discharged to facilities for associated symptom management, involving acute care hospitals, ambulatory surgical centers, outpatient care, and long-term care facilities leading to higher financial burden [26][27][28]. While referring to home or self-care, or post-acute care, patients are at risk of infections [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms that could be related to nosocomial infections were recovered from half of the sampled patients. Cancer patients are submitted to diagnostic and treatment procedures that increase hospital stay, consequently expanding the exposition to pathogen colonization, including multidrug-resistant ones 31 Kamath et al 32 showed a decrease in the oropharyngeal microbiota in HNC patients receiving RT when compared to the control group. Despite the differences among the compared studies, in the majority, microbial recovery occurred inside OM lesions grades III and IV, highlighting the isolation of opportunistic pathogens 28,29,30 .…”
Section: Oral Mucositis Informationmentioning
confidence: 99%